Personality Structure According to Islamic Psychology - I. Arabov (Scientific Trends, 2024)
In Islamic psychology, the concept of personality plays an important role in understanding this field. The human race is a very complex being because it has a physical and metaphysical (spiritual) nature. As for physical characteristics, psychology includes the study of the human race and its personality, while on the spiritual side, it also studies invisible things such as the heart, mind, and spirit of a person. The field of psychology is a scientific field that deals with human behavior. Thus, this article briefly analyzes the concept of the individual in Islam, the Islamic worldview and its relationship with the individual, and the psychology of the individual.
Keywords: Personality, structure of personality, Islamic personality psychology, Islamic psychology.